An Analysis of the Financial Performance Metrics for the Companies Listed on the Iraq Stock Exchange - Elaf Mohmood Abdulrazzaq Al saggar; Mohammed Ghader (Celebes Scholar pg, 2023)
Both theoretical research and analytical investigation are included in the study. To emphasize the significance of this subject in explaining the financial status of businesses, the theoretical study focused on the subject of financial analysis and performance evaluation in general and company performance evaluation in particular. This causes the investor to seek out financial information about businesses, which increases the investor's dependence on these statistics and increases the investor's trust in the businesses that it might invest in. The relevance of financial indicators in assessing a company's liquidity, capacity to pay long- and short-term obligations, and capacity to make a profit was another topic covered in this study (Tahu & Susilo, 2017). Regarding the analytical or practical component, it involved the analysis of a sample from Al-Hamra Insurance Company, an insurance provider registered on the Iraq Stock Exchange. The research arrived at the prospect of relying on the information provided by the company in its latest financial statement after applying financial indicators to the research sample through a re-analysis of its financial performance.